2008
DOI: 10.1149/1.2931522
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic and Local Filming Behavior of AA2024 T3 Aluminum Alloy during Anodizing in Sulfuric Acid Electrolyte

Abstract: The anodic film generated in acid electrolytes on high-purity aluminum shows a porous morphology, formed by the packing of approximately hexagonal cells of alumina, containing a centrally located cylindrical pore. Conversely, during anodizing of an AA2024 T3 alloy, the presence of alloying elements, both in solid solution and as second-phase material, influences the filming behavior, with a less regular film morphology developed above the aluminum alloy matrix, and characteristic morphologies generated above a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
102
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 16 publications
11
102
0
1
Order By: Relevance
“…Cavities and regions of altered film morphology are evident on the surface and associated to the different oxidation behavior of the various metallurgical phases present on the alloy. 23,29,30 After sealing in hot water (Fig. 10b), the surface morphology did not appear substantially different from the one observed on the asanodized specimen.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Cavities and regions of altered film morphology are evident on the surface and associated to the different oxidation behavior of the various metallurgical phases present on the alloy. 23,29,30 After sealing in hot water (Fig. 10b), the surface morphology did not appear substantially different from the one observed on the asanodized specimen.…”
Section: Resultsmentioning
confidence: 74%
“…The current response displayed two peaks during the initial voltage ramp, associated with the oxidation of Al-Mg-Cu and Al-Cu-Fe containing second phase particles, respectively. [23][24][25] During the initial voltage ramp, the current density increased to about 8 mA/cm 2 . As the voltage ramp was interrupted and the constant potential applied, the current decreased slightly, to attain a steady value in the region of 7 mA/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Intermetallic particles in the alloy oxidize at higher or lower potentials than the aluminum matrix during potentiodynamic anodizing in sulfuric acid electrolyte. 5,31,32 The absence of the peak at 0 and 4.8 V confirms the removal of intermetallic particles in the cerium-containing solutions. …”
Section: Resultsmentioning
confidence: 74%
“…The mechanism for the formation of the surface texture during alkaline etching has been reported elsewhere. 18 Anodizing of the alloys of different tempers.-Previous work 8,19 has indicated that intermetallics of different compositions in aluminum alloys are oxidized at specific voltages or voltage ranges. The characteristic voltages/voltage ranges could be determined from the current density-voltage responses of the alloys which were linearly polarized from the OCP to higher voltages.…”
Section: Resultsmentioning
confidence: 99%